A biochemical and structural study of innate immune receptors - Huangfu, Zhiru (Nanyang Technological University, 2023)
Innate immune system can be triggered when there are contagious pathogens, cell damage or tissue injury, which can induce immune responses to eliminate microorganisms, trigger cell proliferations and control infections. Innate immune receptors play a vital role in this process. They can be activated upon ligand recognition, relay signals and recruit downstream proteins to modulate innate immune responses. Some receptors are localized in the nucleus for autoinhibition, being released during infection and regulating host defence. Whereas some are cytosolic receptors, directly interact with adaptor protein after stimulation. Structural investigation into the nucleus interaction of nuclear receptors and downstream adaptor interaction of cytosolic receptors is important in understanding the activation mechanisms of immune receptors. In this thesis, we studied both cytosol receptor (NOD1) and nuclear receptors (IL-33, AIM2 and IFI16). Firstly, we tried to elucidate the interaction mode of NOD1 CARD and its adaptor RIP2 CARD by solving the structure of recombinant fusion protein, RIP2 CARD-NOD1 CARD. Using electron microscopy, it was found to form heterogenous complexes, suggesting that unstable formation of two CARD domains. Secondly, the associations of nucleosome with Interleukin-33, AIM2 and IFI16 were investigated. This was achieved by the biochemical and structural study of IL-33-, AIM2- and IFI16- NCP complexes. EMSA showed the binding affinity of proteins to NCP, but processing of Cryo-electron microscopy dataset showed no extra density besides NCP. Our study can provide new insights into existing knowledge of signalling pathway of NOD1 and the autoinhibition status of nuclear receptors.